2012
DOI: 10.1161/hypertensionaha.112.200337
|View full text |Cite
|
Sign up to set email alerts
|

Death-Associated Protein Kinase 3 Mediates Vascular Inflammation and Development of Hypertension in Spontaneously Hypertensive Rats

Abstract: C almodulin (CaM) is recognized as a key regulatory molecule for diverse biological functions, such as muscular contraction.1 In addition, a recent study demonstrated that CaM-dependent protein kinases, such as CaM-dependent protein kinase II, may regulate hypertension through the mechanisms including promotion of vascular smooth muscle hypertrophy. 2 In the previous study, we compared expression levels of several CaM-related proteins with almost unknown functions in vasculature. As a result, we demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…Because previous reports demonstrated that NO-mediated endothelium-dependent relaxation was impaired in the artery from SHR [6,11,12], this observation may support the idea that the effect of omentin was endothelial NOdependent. However, since our previous results suggested the NO-independent component of vasodilation by omentin in isolated blood vessel [15], we cannot completely exclude the possibility that omentin may reduce the agonists-induced increases in BP via NO-independent mechanisms.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Because previous reports demonstrated that NO-mediated endothelium-dependent relaxation was impaired in the artery from SHR [6,11,12], this observation may support the idea that the effect of omentin was endothelial NOdependent. However, since our previous results suggested the NO-independent component of vasodilation by omentin in isolated blood vessel [15], we cannot completely exclude the possibility that omentin may reduce the agonists-induced increases in BP via NO-independent mechanisms.…”
Section: Discussionsupporting
confidence: 74%
“…Body weight, heart rate (HR), systolic blood pressure (BP) (SBP), mean BP (MBP) and diastolic BP (DBP) represent the average value (Table 1). Noninvasive BP in conscious rats was measured using a tail-cuff method after heating the rats (38°C) (Softron, Tokyo, Japan) [6,11,12]. L-NAME was dissolved in drinking water and given to rats (80 mg/kg, 1 day).…”
Section: Methodsmentioning
confidence: 99%
“…15 We wondered whether the responses of mesenteric arteries to phenylephrine and KPSS stimuli were different between SHRs and Wistar Kyoto (WKY) rats after mitochondrial fission inhibition. SHRs showed increased systolic blood pressure, diastolic blood pressure, and heart body ratio ( Figure S10A and S10B).…”
Section: Pharmacological Drp1 Inhibition Antagonizes Phenylephrine-anmentioning
confidence: 99%
“…27 SHR exhibited more profound inflammatory status in mesenteric arteries. 28 NF-kB and VCAM-1 both actively participate in vascular inflammation. 29 The increased expression of VCAM-1 is a marker of vascular inflammation, vascular permeability, and endothelial dysfunction, [30][31][32] and the NF-kB is a well-studied regulator for inflammation.…”
Section: Cdca Treatment Increased Vcam-1 Expression and Nf-kb Activitmentioning
confidence: 99%